Role of Training in Transferring Rice Production Technologies to Farm Level - Hossain, MS; Islam, AKMS; Kabir, MJ; Sarkar, MAR; Mamun, MAA; Rahman, MC; Salam, MU; Kabir, MS (Bangladesh Rice Journal, 2021)
Farmers' knowledge gap in modern rice cultural practice is the main cause of the existing yield gap in Bangladesh. Thus, this paper delineates; (i) the level of farmers’ knowledge gap; (ii) assesses the impact of training on changes in the farmers' skills, knowledge as well as technology adoption, and crop performance. Finally propose an approach for improving farmers’ skills on modern rice cultural practices through fruitful training. Secondary data, in particular, journal articles were reviewed and analyzed in the paper. From the analysis, we found that majority of the farmers (85%) belong to the medium level of the overall knowledge gap category. There was a significant increase in the knowledge and skills of farmers after undertaking the training. As a result, the rice yield of trained progressive farmers increased to 4.7 t ha-1 in 2012 from 3.1 t ha-1 in 2008. However, the rice yield of ordinary trained farmers increased to 3.7 t ha-1 in 2012 from around 2.6 t ha-1 in 2008. The traditional extension approach was less efficacious to improve farmers' knowledge gap and disseminate the rice production technologies to the farm level. Therefore, strengthening BRRI's capacity to provide seed to seed training to most of the DAE personnel to upgrade their skills on modern rice technologies is critically important. Besides, demonstrations based farmers training might be highly productive in transferring modern rice production technologies to the farmers. Bangladesh Rice J. 25 (1) : 111-120, 2021